mpowerment Level of Employed Women in Decision Making - Priyanka,; Tigga, Adline Shanta; Kumari, Monika (Indian Journal of Extension Education, 2019)
Empowerment of women has been recognized as a central issue in determining the status of women. The role of employed women has changed throughout the country and the world due to economic conditions and social demands. Employed women have tremendous pressure to develop their career as robust as their male counterparts while sustaining active engagement in personal life. Economic empowerment is the capacity of women to participate in, contribute to and benefit from growth process in ways which recognise the value of their contribution, respect their dignity and make it possible to negotiate a fairer distribution of the benefits of growth. Employment empowers women by providing financial independence, alternative source of social identity and exposure to power structures. In the economic sphere, paid employment is seen as essential to women’s empowerment which focuses on access to employment opportunities and working conditions at work place and at community level, and on a woman’s decision making power freedom of movement, control over resources and contribution to total family earnings in the household. This paper is an attempt to know the extent of empowerment of employed women. It was measured by four indicators of women empowerment. It was found that empowerment of employed women was in medium level under empowerment index. It concluded that there are number of structural barriers which limit the extent of empowerment.
Keywords: Employment; Empowerment; Economic empowerment